2014
DOI: 10.1158/2326-6066.cir-13-0181
|View full text |Cite
|
Sign up to set email alerts
|

MEK Inhibition, Alone or in Combination with BRAF Inhibition, Affects Multiple Functions of Isolated Normal Human Lymphocytes and Dendritic Cells

Abstract: Combination therapy with BRAF and MEK inhibition is currently in clinical development for the treatment of BRAF-mutated malignant melanoma. BRAF inhibitors are associated with enhanced antigen-specific T-lymphocyte recognition in vivo. Consequently, BRAF inhibition has been proposed as proimmunogenic and there has been considerable enthusiasm for combining BRAF inhibition with immunotherapy. MEK inhibitors inhibit ERK phosphorylation regardless of BRAF mutational status and have been reported to impair T-lymph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
99
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 47 publications
14
99
1
Order By: Relevance
“…In this study, we assessed the immunologic effects of dabrafenib and trametinib at clinically relevant exposures on both immune and tumor cells in vitro. The effect on immune cells by dabrafenib was consistent with the literature reports for BRAF inhibitors (10,11). However, we found that the effect of trametinib on immune cells was both complex and context dependent.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we assessed the immunologic effects of dabrafenib and trametinib at clinically relevant exposures on both immune and tumor cells in vitro. The effect on immune cells by dabrafenib was consistent with the literature reports for BRAF inhibitors (10,11). However, we found that the effect of trametinib on immune cells was both complex and context dependent.…”
Section: Introductionsupporting
confidence: 91%
“…Preclinical and limited clinical findings have suggested that immunomodulatory effects in the tumor microenvironment and on circulating immune cells by a BRAF inhibitor alone and the combination of a BRAF inhibitor with a MEK inhibitor is context-dependent (8,(17)(18)(19)(20). On the other hand, concerns have been raised regarding the potential immunosuppressive activity of MEK inhibitors due to their immunosuppressive activity in vitro (10). However, the studies have been limited in scope and lack in vivo validation in mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was particularly important as previous studies have shown that MEK inhibitors are potentially immunosuppressive (40,41). We found no evidence for marked immunosuppressive effects in the TILs in the sequential biopsies taken from patients treated with Combi, which appeared comparable to those in patients treated with BRAFi monotherapy.…”
Section: Discussionsupporting
confidence: 53%
“…5 While our results with dabrafenib were similar to the reported effects of vemurafenib on T lymphocytes, the BRAFi BMS908662, has been shown to enhance T-cell proliferation 6 (and reviewed in). 3 Furthermore, a recent retrospective analysis of peripheral lymphocytes reported that vemurafenib, but not dabrafenib, -treated patients had decreased peripheral lymphocyte counts and altered CD4 C T-lymphocyte phenotype and function, as compared with baseline samples.…”
supporting
confidence: 83%